The subject of the truth in a criminal proceeding (Journal of actual problems of jurisprudence, 2018)
In this article, the truth is seen as credible by all means worthy of full and unquestioned trust in her. And this truth is able to be only the truth, not just confirmed, even the most perfect, the evidence, but certainly certified in compliance with all other principles and guarantees of due legal procedure. By its nature, the truth in criminal proceedings is an objective truth, ie, the content of the findings of the inspector and the court about the circumstances of the case, which does not depend on their desires and impulses, and must conform to the objective reality.Key words: objective truth, evidence, criminal procedure, knowledge.